Manganese Superoxide Dismutase V16A Single-Nucleotide Polymorphism in the Mitochondrial Targeting Sequence Is Associated with Reduced Enzymatic Activity in Cryopreserved Human Hepatocytes - Martin, Robert C.G. (Mary Ann Liebert, Inc., 2009)
Mitochondrial manganese superoxide dismutase (MnSOD), encoded by the SOD2 gene, represents a major cellular defense against environmental carcinogens that cause oxidative stress. Two single-nucleotide polymorphisms −9 T>C (V16A in the MnSOD mitochondrial targeting sequence) and −102 C>T (in the SOD2 promoter sequence) modify risk toward various types of malignancies and overall survival. Since little is known about the effects of these polymorphisms on overall enzyme function in normal human tissue, the goal of this study was to evaluate their functional effects in cryopreserved human hepatocytes. Cryopreserved human hepatocytes were genotyped for the MnSOD −9 T>C and −102 C>T polymorphisms by TaqMan allelic discrimination assays. MnSOD catalytic activities were determined in vitro in lysates derived from the hepatocytes. In random samplings of cryopreserved hepatocytes, 16% possessed the −9 T>C and 6% possessed polymorphism on at least one of the two alleles. −9 T>C (V16A) significantly (p < 0.02) reduced MnSOD catalytic activity whereas −102 C>T did not (p > 0.05). The −9 T>C (V16A) polymorphism in the MnSOD mitochondrial targeting sequence significantly reduced MnSOD catalytic activity in cryopreserved hepatocytes, consistent with its reported associations with cancer risk and treatment.